Traumatic Lumbosacral Dislocation: Current Concepts in Diagnosis and Management - Andrew S. Moon; Kivanc Atesok; Thomas E. Niemeier; Sakthivel R. Manoharan; Jason L. Pittman; Steven M. Theiss (Advances in Orthopedics)
Traumatic lumbosacral dislocation is a rare, high-energy mechanism injury characterized by displacement of the fifth lumbar vertebra in relation to the sacrum. Due to the violent trauma typically associated with this lesion, there are often severe, coexisting injuries. High-quality radiographic studies, in addition to appropriate utilization of CT scan and MRI, are essential for proper evaluation and diagnosis. Although reports in the literature include nonoperative and operative management, most authors advocate for surgical treatment with open reduction and decompression with instrumentation and fusion. Despite advances in early diagnosis and management, this injury type is associated with significant morbidity and mortality, and long-term patient outcomes remain unclear.